GUIDELINES FOR PROMOTIING SUSTAINABLE EMPLOYMENT OF PERSONS WITH DISABILITIES - Norasethaporn, Chartchai (Academic Journal Phranakhon Rajabhat University, 2022)
Thailand had a vision for developing the quality of life among persons with disabilities and realized their problems. Consequently, the Empowerment of Persons with Disabilities Act, B.E. 2550 (2007) was enacted, particularly the provision 33, 34, and 35 which emphasized the employment, career promotion, and direct employment protection of persons with disabilities. Nevertheless, only 36.83 percent of persons with disabilities had job. From the study on problems of employment of persons with disabilities gained from both public and private sectors, there were sustainable solutions for developing the employment of persons with disabilities: 1) data management related to persons with disabilities of the Department of Empowerment of Persons with Disabilities and Department of Employment should be linked, 2) law amendment should be done to guarantee the employment of persons with disabilities, 3) regulations for approving the employment project for persons with disabilities based on the provision 35 should be relaxed in order to sustainably increase the employment opportunities for persons with disabilities, 4) claim of rights regarding the empowerment of persons with disabilities according to the provision 35 should be amended, revised, and adapted, 5) registration with the associations and foundations of persons with disabilities was recommended in order to enhance the cooperation and supervision, 6) government agencies should regularly provide knowledge to the enterprises, 7) all public agencies should coordinate for the preparation and potential development of persons with disabilities, 8) special benefits should be granted to private providers in education for the preparation and potential development of persons with disabilities, and 9) incentive programs should be generated to the organization that employed persons with disabilities beyond the number allowed by law.